Ebussuud Efendi’nin Osmanlı hukukundaki yeri - Demir, Abdullah (My University, 2004)
Ebussuud Efendi Osmanlı İmparatorluğu'nun en büyük hukukçularından birisidir. O sekiz yıl Rumeli Kazaskerliği ve otuz yıl da Şeyhülislamlık yapmıştır. Ebussuud Efendi kanunla şer'i hukuku uyumlu hale getirmiştir. Dönemin padişahı Kanuni Sultan Süleyman'ın desteğiyle hukuku şekillendirmiştir. Bu çalışmanın amacı Şeyhülislam Ebussuud Efendi'nin Osmanlı hukukundaki yerini ortaya koymaktır. Bu çalışma altı bölümden oluşmaktadır: Ebussuud Efendi'nin hayatı- Dönemin sosyal, ekonomik, siyasî ve dinî durumu- Ebussuud Efendi'nin arazi ve vergi hukukundaki yeri- Ebussuud Efendi'nin yargılama hukukundaki görüşleri- Ebussuud Efendi'nin vakıfla ilgili görüşleri- genel değerlendirme.

Ebussuud Efendi (896-982/ 1490-1574), is one of the prominent jurists of the Ottoman State. He was Military Judge of Rumelia for eight years and Sheikhulislam for thirty years. Ebussuud Efendi succeeded in bringing the kanun into agreement with sharia. Supported by Kanuni Sultan Süleyman, he completed and consolidated a development of law. The aim of this study is to explain the place of Ebussuud Efendi in the Ottoman Law. In Our study is existence of six chapter: The life of Ebussuud Efendi- the social, economic, political and religious situations in the Ottoman State- the studies of Ebussuud Efendi in the land tenure an taxation- the opinions of Ebussuud Efendi in the judicial functions- the opinions of Ebussuud Efendi in the foundation-general interpretation.
Keywords: Ebussuud Efendi,1490?_1574?; Kamu Hukuku_Türkiye